PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR PADA PENDIDIKAN KEWARGANEGARAAN - M Choirul Muzaini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to determine whether there is an effect of a Contextual Teaching and Learning learning model on student learning outcomes in civic education learning. This research method is a pre-experimental type of one-group pretest-postest with a quantitative approach. Data collection techniques are through observation, tests, and documentation. Based on the results of the n-gain test, there are 6 students or 46% of students in Citizenship Education learning there is an increase with very satisfying criteria, while 3 students or 23% of students there is an increase with standard criteria, and 1 student or 8% of students there is an increase with low criteria, while 3 students or 23% of students there is an increase with stagnant criteria. The n-gain value obtained an average magnitude of 0.6, thus learning Citizenship Education has increased with standard criteria. So a red thread can be drawn in this study, that the Contextual Teaching and Learning learning model has an influence on the learning outcomes of Citizenship Education for students.